CGIAR Climate Impact Platform Amplifies the Need for Just Transitions in the Agri-Food Sector by Advocating Within Global Climate Processes in 2024 - Edward-Uwadiale, Regina (CGIAR Climate Change Impact Platform, 2024)
The CGIAR Climate Impact Platform has emerged as a key voice in advocating for just transitions in the agri-food sector, underscoring its critical role in addressing the challenges of climate change. Drawing from its robust engagements at COP29 and other global platforms, the Platform has actively contributed to shaping the global climate discourse through a series of impactful activities, including high-level events, thought-provoking op-eds, blog publications, and thematic webinars. By fostering collaborations with diverse stakeholders, the Platform has amplified the urgency of equitable climate adaptation and mitigation strategies within the agri-food systems. This report explores how the Platform’s initiatives have reinforced the need for inclusive transitions that prioritize the needs of vulnerable populations, highlight sustainable agricultural practices, and align with broader climate goals.